Kebangkitan China melalui Belt and Road Initiative dan (Re)konstruksi Hubungan Internasional dalam Sistem Westphalia - Johni Robert Verianto Korwa (Universitas Muhammadiyah Yogyakarta, 2019)
This paper aims to examine the rise of China with the use of Chinese philosophical world concept called ‘all under heaven’ (tianxia). Even though the concept is outdated, it remains vitally important to understand how China behaves and sees the world today. This paper argues that China will continue to rise and reconstruct International Relations as a discipline based on the tianxia perspective with Belt and Road Initiative (BRI) as an instrument to achieve it. This paper finds that not only does BRI help the rise of China in recent years, it also weakens the concept of Westphalia adopted by western countries. This paper contends China will rise peacefully in terms of economic sector, not the military. In addition to this, the U.S. strategy of 'free and open Indo-Pacific' remains weak in responding to BRI as well as containing the rise of China.